Analisis Pencahayaan 3 Point Lighting pada Film Autobiography Sutradara Makbul Mubarak - M. Fajar Aditya; Dani Manesah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
Lighting plays a crucial role in film production, not only providing illumination for subjects but also creating atmosphere, conveying emotions, and supporting the narrative. This study analyzes the application of the 3 Point Lighting technique (Key Light, Fill Light, Back Light) in the film Autobiography directed by Makbul Mubarak. Using a qualitative approach and descriptive method, this research explores how lighting highlights the emotions of the main character, Rakib, and creates visuals that enhance the storyline. The results show that the 3 Point Lighting technique effectively conveys dramatic moods, such as confusion, sadness, and emptiness, experienced by the main character. This technique not only strengthens character development but also delivers an immersive visual experience for the audience. This study aims to provide insights for filmmakers in utilizing lighting as an aesthetic and effective visual communication tool.